ASSA13-03-7 Renal Sympathetic Denervation Changes the Distribution of Atrial Substrate and Inhibites the Inducibility of Atrial Fibrillation. (29th April 2013) - Zhao, Qingyan; Dai, Zixuan; Yu, Shengbo; Wang, Xule; Xiao, Jinping; Huang, Congxin
Abstract : Objective: Whether renal sympathetic denervation has effect on changes of atrial substrate and inducilibity of atrial fibrillation is unknown. The purpose of this study was to determine the effect of renal denervation on the inducibility atrial fibrillation. Methods: Thirteen dogs were randomly divided into control group (7 dogs) and renal artery ablation group (6 dogs). In control group, at first, atrial fibrillation was induced by anterior right ganglionated plexi stimulation. Then, rapid atrial pacing was performed for 7 hours. Atrial effective refractory period and atrial fibrillation were measured each hour. In renal artery ablation group, after renal artery ablation, dogs were raised for 6 weeks. After that, the procedure of pacing and electrophysiological measurement was same as in the control group. Results: The voltage in the sinus rate slowing response and the threshold of inducilibity atrial fibrillation increased during ganglionated plexi stimulation after renal artery ablation (3.5 ± 1.6V vs 1.6 ± 0.3V; 5.1V ± 1.0V vs 2.1V ± 0.7V, P = 0.03). Induced number of times and duration of atrial fibrillation was higher in control group than that in renal artery ablation group after cessation of pacing. Levels of ANP in right atrium and densities of Cx43 were lower in renal artery ablation group than that in control group (ANP: 220.5 ± 37.6 pg/mg vs 164.4 ± 22.0 pg/mg, P = 0.02; Cx43: 0.52, 0.63, 0.87 vs 1, 1.02, 1.91, P < 0.01). Conclusions: Renal sympathetic denervation results in changes of atrial substrate and markedly decrease the inducilibity of atrial fibrillation by inhibiting activity of renin-angiotensin-aldosterone system.